Program Penguatan Kompetensi Guru dalam Pembelajaran Berbasis Proyek (Project Based Learning) SMKN 4 Bandung: Pengabdian - Fresa Dwi Juniar Sofalina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to improve the competency of teachers at SMK Negeri 4 Bandung in implementing project-based learning (PBL). The background to this activity is the need to adapt learning methods to be more contextual and encourage 21st-century skills for vocational school students, especially in facing the demands of the world of work and the implementation of the Independent Curriculum. The implementation method includes a preparation stage (needs mapping and module development), a training stage (material delivery and practical simulations), and a mentoring stage (project implementation in class and evaluation). Evaluation was conducted through pre- and post-tests as well as direct observation of classroom learning implementation. The results of the activity showed a significant increase in all aspects of teacher competency, with an average post-test score increasing by more than 25 points compared to the pre-test. Teachers also demonstrated enthusiasm in designing and implementing project-based learning relevant to their respective areas of expertise. Documentation of the activity reflects the active involvement of participants, both in training sessions and during project implementation in class.